ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN TUBERCULOIS DI WILAYAH KERJA PUSKESMAS CENDANA PUTIH KECAMATAN MAPPEDECENG KABUPATEN LUWU UTARA - Nansorina, Three Novi; Baharuddin, Baharuddin; Musfirah, Musfirah (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2024)
Tuberculosis is a chronic infectious disease caused by Mycobacterium tuberculosis which spreads through the air when an infected person coughs, sneezes or spits. Based on 2022 data, it is estimated that 10.6 million people will be infected with Tuberculosis in 2022, an increase of 4.5 percent from 10.1 million people in 2021. The research method uses quantitative research with a Cross Sectional Study approach with 358 populations and 189 samples, sampling using the Slovin formula and simple random sampling techniques. Data analysis was carried out univariate and bivariate using the chi-square test. The results of the study showed that there was a significant relationship between family history (p-value 0.038) and residential density (p-value 0.024) with the incidence of tuberculosis. However, no significant relationship was found between age (p-value 0.196) and family income (p-value 0.222) and the incidence of tuberculosis. Conclusions of study This is that history family and density residence own significant relationship with incident tuberculosis, transient age and income family No own significant relationship at the work area Puskesmas Cendana Putih Mappedeceng District North Luwu Regency. Expected For alert to transmission of tuberculosis with method guard immune wear a mask and limit contact with sufferer